2008
DOI: 10.1111/j.1365-2133.2008.08787.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated 5-aminolaevulinic acid-photodynamic therapy vs. surgical excision in the treatment of nodular basal cell carcinoma: results of a randomized controlled trial

Abstract: SE proved to be significantly more effective than treatment with fractionated illumination ALA-PDT. Therefore, in the treatment of primary nBCC, SE is preferred over PDT following this treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 32 publications
5
85
1
3
Order By: Relevance
“…Also recurrence-free survival was lower with greater tumour thickness [24]. Furthermore, previous research showed that invasive SCC as well as nodular BCC have low overall success rates after PDT [19,25]. These findings suggest that increased epidermal thickness might play a significant role in BD too.…”
Section: Discussionmentioning
confidence: 58%
“…Also recurrence-free survival was lower with greater tumour thickness [24]. Furthermore, previous research showed that invasive SCC as well as nodular BCC have low overall success rates after PDT [19,25]. These findings suggest that increased epidermal thickness might play a significant role in BD too.…”
Section: Discussionmentioning
confidence: 58%
“…The 5-aminolevulinic acid-(ALA-) PDT is significantly inferior to surgery for treatment of nodular BCC (3-year clearance rates of 70% and 98%, respectively), 61 although it may still play a role in treating superficial BCC. Studies comparing MAL-PDT with ALA-PDT are needed to further refine treatment protocols.…”
Section: 60mentioning
confidence: 99%
“…Fractionated ALA-PDT is comparable to surgery in clearing nBCC. However, failure rates during long-term follow-up vary between 20 and 31 % at 2-5 years depending on fractionated dosing protocol and debulking pretreatment (de Haas et al 2007(de Haas et al , 2008Mosterd et al 2008 ;Roozeboom et al 2013 ).…”
Section: Nodular Basal Cell Carcinomamentioning
confidence: 98%